2019
DOI: 10.1149/2.1231915jes
|View full text |Cite
|
Sign up to set email alerts
|

P2 Type Layered Solid-State Electrolyte Na2Zn2TeO6: Crystal Structure and Stacking Faults

Abstract: The layered super-ionic conductor Na2Zn2TeO6 is a promising material for applications as electrolyte in solid-state batteries. Independent of synthesis route and conditions, a significant peak broadening of (1 0 1) is evident in collected X-ray diffraction data, which is not compatible with the standard structure model (space group P6322). In this work, we describe sodium disorder and stacking faults in Na2Zn2TeO6 and identify the nature of the faults that are manifested by this peak broadening. First principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…Crystallographic information for the involved P2 and O′3-type phases is summarized in Tables S4 and S5. Note that the still imperfect fit of the diffraction peaks in the 2θ-range 3.5–5.0° is due to the presence of stacking faults in the P2-type phase, or possibly a P2/O′3–type composite as described by Guo et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic information for the involved P2 and O′3-type phases is summarized in Tables S4 and S5. Note that the still imperfect fit of the diffraction peaks in the 2θ-range 3.5–5.0° is due to the presence of stacking faults in the P2-type phase, or possibly a P2/O′3–type composite as described by Guo et al…”
Section: Resultsmentioning
confidence: 99%
“…These two structure types are related by an in-plane shift of one of the ( M 2 Te) n layers. In our recent work, we have shown that these two types of stacking coexist in Na 2 Zn 2 TeO 6 (NZTO) . The materials with M = Zn and Mg are considered as ideal candidates for application as solid-state electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…412 Experimental and theoretical reports on the structures of these materials has already revealed some stacking disorders with honeycomb layered species such as Na 3 Ni 2 SbO 6 , Na 2 Zn 2 TeO 6 and Na 2 Ni 2 TeO 6 , associating them with emergent functionalities such as phase transitions, magnetic ground states and ionic diffusion. 60,170,253,413 Although defects have been known to have both prolific and detrimental effects on honeycomb layered oxides, they still remain vastly underexplored. Nonetheless, de novo computational and experimental techniques are expected to uncover new defect physics and chemistry that will expand their uses into multiple fields.…”
Section: Summary and Future Challenges For Honeycomb Layered Oxidesmentioning
confidence: 99%
“…Although the integral of Peak2 obviously increases with elevated temperature, the fractions of Peak2 are quantified as 0.41±0.03 based on VOCS spectra at variable temperatures (Figure 4 b) after taking into account the transverse relaxation effects during the echo periods [37] . Given that no transform between P 6 3 / mcm and P 6 3 22 by interlayer slipping is expected in such a narrow variable temperature range, [38] two isotropic shifts may correspond to interlayer averaged 23 Na shift of P 6 3 / mcm and P 6 3 22, respectively.…”
Section: Resultsmentioning
confidence: 99%